The Accuracy of Labor - Kotany, L. (Quarterly Journal of Economics, 1920)
I. All products inaccurate; need of tolerance, 687. — Tactile pressure, and its delicacy in arts and crafts, 688. — II. Physiological causes of differences between individuals in accuracy of work, 690. — Memory and attention, 691. — No measure of accuracy or of labor, 693. — III. Differences in wages based on differing accuracy, 695. — Division of labor on that basis, 696.